Liver-Specific Alpha 2 Interferon Gene Expression Results in Protection from Induced Hepatitis - Aurisicchio, Luigi (American Society for Microbiology, 2000)
The current therapy for hepatitis B and C is based on systemic administration of recombinant human alpha interferon (r-hIFN-α). However, systemic delivery of r-hIFN-α is associated with severe side effects, but more importantly, it is effective in only a small percentage of patients. In an effort to maximize IFN-α antiviral efficacy, we have explored the therapeutic potential of murine IFN-α2 (mIFNα2) selectively expressed in the liver. To this end, we have developed a helper-dependent adenovirus vector (HD) containing the mIFN-α2 gene under the control of the liver-specific transthyretin promoter (HD-IFN). Comparison with a first-generation adenovirus carrying the same mIFN-α2 expression cassette indicates that at certain HD-IFN doses, induction of antiviral genes can be achieved in the absence of detectable circulating mIFN-α2. Challenge of injected mice with mouse hepatitis virus type 3 showed that HD-IFN provides high liver protection. Moreover, liver protection was also observed in acute nonviral liver inflammation hepatitis induced by concanavalin A at 1 month postinfection. These results hold promise for the development of a gene therapy treatment for chronic viral hepatitis based on liver-restricted expression of IFN-α2.